Chronic Granulomatous Disease (CGD): Commonly Associated Pathogens, Diagnosis and Treatment - Angel A. Justiz-Vaillant; Arlene Faye-Ann Williams-Persad; Rodolfo Arozarena-Fundora; Darren Gopaul; Sachin Soodeen; Odalis Asin-Milan; Reinand Thompson; Chandrashekhar Unakal; Patrick Eberechi Akpaka (Microorganisms, 2023)
Chronic granulomatous disease (CGD) is a primary immunodeficiency caused by a defect in the phagocytic function of the innate immune system owing to mutations in genes encoding the five subunits of the nicotinamide adenine dinucleotide phosphatase (NADPH) oxidase enzyme complex. This review aimed to provide a comprehensive approach to the pathogens associated with chronic granulomatous disease (CGD) and its management. Patients with CGD, often children, have recurrent life-threatening infections and may develop infectious or inflammatory complications. The most common microorganisms observed in the patients with CGD are Staphylococcus aureus, Aspergillus spp., Candida spp., Nocardia spp., Burkholderia spp., Serratia spp., and Salmonella spp. Antibacterial prophylaxis with trimethoprim-sulfamethoxazole, antifungal prophylaxis usually with itraconazole, and interferon gamma immunotherapy have been successfully used in reducing infection in CGD. Haematopoietic stem cell transplantation (HCT) have been successfully proven to be the treatment of choice in patients with CGD.